Pieśń o stworzeniu człowieka. Refleksje egzegetyczno-teologiczne nad tekstem Rdz 1, 26-28 i 2,7. 15. 18. 21-23 - Homerski, Józef (The Biblical Annals, 2017)
The Yahwistic version of the creation of man lays stress on the „breath of God,” i.e. the spiritual element, which out of matter (out of the clay of the ground) made the human creature alive, and on the identity of the nature of the woman who, together with her husband, makes up a supportive and complementary fellowship and the smallest social unit. The song in the sacerdotal version says that man was created as a creature with which God may and wants to enter into a dialogue. The difference in sex comes from God and points that man and woman, having the same nature of the will of the Creator Himself. They have different tasks in their lives, which is related with the difference in sex. Labour is a gift given from God, and their ultimate goal is to rest with God and in God.